MASSASE COUNTER PRESSURE PADA PENGURANGAN NYERI PERSALINAN KALA I - Vera Yuanita; Rohani; Herliza Inda Kurnia (Jurnal Kesehatan dan Pembangunan, 2023)
The birthing process is the process of expelling the fetus, placenta, and membranes through birth canal from the uterus. The birth process begins with the opening and dilatation of the cervix that give rise to contractions of systematic frequency, duration, and strength. Labor pain can be treated by pharmacological and non-pharmacological methods. One of the non-pharmacological treatments can be done with massage techniques counter pressure. The purpose of this research is to describe effectiveness of counter pressure massage in reducing labor pain in the first stage. Design This research is using literature study method. Deep data source This study uses secondary data obtained by conducting studies literature from journals that are appropriate to the research topic from 2018-2022 6 journals. Based on the review literature conducted by the author, it can be concluded that massage counter pressure is effective in reducing labor pain when 1. It is hoped that the suggestions can be forwarded and taught to clients of pregnant women Families who experience labor pain in the first stage can apply a massage counter pressure as a method of reducing labor pain in the first stage of labour.